2002
DOI: 10.1007/bf02345072
|View full text |Cite
|
Sign up to set email alerts
|

Systematic comparison of different algorithms for apnoea detection based on electrocardiogram recordings

Abstract: Sleep apnoea is a common disorder that is usually diagnosed through expensive studies conducted in sleep laboratories. Sleep apnoea is accompanied by a characteristic cyclic variation in heart rate or other changes in the waveform of the electrocardiogram (ECG). If sleep apnoea could be diagnosed using only the ECG, it could be possible to diagnose sleep apnoea automatically and inexpensively from ECG recordings acquired in the patient's home. This study had two parts. The first was to assess the ability of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
203
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(217 citation statements)
references
References 25 publications
5
203
0
9
Order By: Relevance
“…A recent study reported 86.6% Acc and 0.941 AROC for a LR classifier modelling with four clinical variables and one symbolic dynamic feature extracted from HRV [57]. Finally, several works have reported 100% Acc when classifying 30 subjects from the PhysioNet Apnea-ECG database, which was used in the Computers in Cardiology Challenge 2000 [58]. However, comparison with studies using this database is difficult since borderline subjects were deliberately removed from the competition.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported 86.6% Acc and 0.941 AROC for a LR classifier modelling with four clinical variables and one symbolic dynamic feature extracted from HRV [57]. Finally, several works have reported 100% Acc when classifying 30 subjects from the PhysioNet Apnea-ECG database, which was used in the Computers in Cardiology Challenge 2000 [58]. However, comparison with studies using this database is difficult since borderline subjects were deliberately removed from the competition.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis typically requires a polysomnogram, an expensive and often uncomfortable in-clinic test. The results of the challenge demonstrate that a variety of methods for analyzing an ambulatory ECG recording, which can be obtained for a tenth of the cost at home with little or no discomfort, are just as reliable for diagnosis of sleep apnea (27,28).…”
Section: Challenge 2000: Detecting Sleep Apnea From the Electrocardiomentioning
confidence: 99%
“…One objective of this challenge was to quantify the apnea stress by the number of minutes spent with disordered breathing. The surprisingly good results and methods are summarized in (11).…”
Section: Introductionmentioning
confidence: 99%